INTEGRATED MODELS OF CONSTRUCTION MANAGEMENT BASED ON BIM FOR REDUCTION OF REWORK IN CIVIL CONSTRUCTION: PROPOSAL OF A RETURN ON INVESTMENT (ROI) EVALUATION FRAMEWORK - Araújo Silva Duarte, Niânylla (Revista Gênero e Interdisciplinaridade, 2025)
The high incidence of rework in Civil Construction (CC) represents one of the greatest obstacles to productivity and profitability in the sector, with costs that can vary from 1% to 20% of the total project value (PLANRADAR, 2020). This article proposes and analyzes an Integrated Construction Management Model (MIGO) based on Building Information Modeling (BIM) methodology, integrating it with Lean Construction (LC) principles and the use of a Common Data Environment (CDE), with primary focus on the prevention and reduction of rework. The methodology employed consisted of a systematic literature review and the adaptation of a Return on Investment (ROI) evaluation framework for BIM, originally proposed by Lee and Lee (2020). The results of the analysis indicate that the proposed MIGO-BIM enhances the detection of interferences and project compatibility in the initial phases, resulting in a significant reduction of rework. The application of the ROI framework demonstrates a primary ROI potential of 167.8% (based exclusively on rework prevention) and an integrated ROI of 476.72%, when considering broader benefits (LEE; LEE, 2020). It is concluded that MIGO-BIM, supported by a robust evaluation framework, offers a strategic tool for proactive project management, transforming BIM from a mere modeling tool into a quantifiable integrated management system.